If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 2u = u Solving -7 + 2u = u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. -7 + 2u + -1u = u + -1u Combine like terms: 2u + -1u = 1u -7 + 1u = u + -1u Combine like terms: u + -1u = 0 -7 + 1u = 0 Add '7' to each side of the equation. -7 + 7 + 1u = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 1u = 0 + 7 1u = 0 + 7 Combine like terms: 0 + 7 = 7 1u = 7 Divide each side by '1'. u = 7 Simplifying u = 7
| 6x-23=4x+41 | | 3y-2=-19+4y | | 24c^3+12c^2-12c+6=0 | | (X+25)=(x-10) | | 12x+20=8x+40 | | 28-8x=-60 | | (5/12)x-1=(2/3)x=5 | | 5x+20-8=7 | | -3y-9x=-15 | | 3x-6=-32 | | 8y+2=4x-2 | | 36s^2+12s+36=35 | | 36s^2+12s+36=0 | | M/2=2.5 | | 1.2=c/4 | | -15+2x-14x=2x+1 | | 40.3=b/7 | | 2=a/15-1 | | 5.4=-t/9.5 | | 81650.99=2*3.14*r*r+2*3.14*r*287.8 | | X+2x+30= | | 2n/7-5=1 | | 4.7=-3.4-5.5-3.4-5.5 | | 2-(-13.5/3) | | 2/3×1/2×=7 | | 17x-5=12x-20 | | 9x-8=72 | | 3.25+y=5.75 | | 2+4(12v+7)-4v= | | 4y+12=-x | | 9+9c=-13 | | 584387492947+584387492947999999999999999999998=x |